Postharvest application of polyamines influence ripening related changes and ameliorate chilling stress in carambola during cold storage - Ahmad, Azhane (2018)
Malaysian carambola (Averrhoa carambola L.) B10 variety is one of the promising exotic tropical fruit traded in the global market. The alarming demand for carambola was stimulated by its unique shape and flavour, increasing health consciousness and great potential in fresh-cut industry. Nevertheless, carambola is a highly perishable commodity that greatly impairs its postharvest quality and long term storability. Therefore, investigations were carried out to verify the potential of putrescine (PUT), spermidine (SPD) and spermine (SPM) as a postharvest dip treatment for maintaining quality, reducing chilling injury (CI) and extending the storage life of carambola.